Reducing Catheter-Associated Urinary Tract Infections: Nursing Interventions and Prevention - Abdulaziz Mulfi Khalawi Almutairy(7)Abdullah Barakah ALmatairi (8)Abdoulrazaqa Mualaa Sultan Almutairi(9)Majed Nafe Mogaeed Almutairi (10)Hanan Tajer Dukhain Alanazy(11)Nawwaf Mohammed Al-Rashidi(12), Ahmed Salem Sulaiman Alharbi (1)Fahd Jameel Ali Al-Rubaie (2)Dalal Mubarak Fahad Alshamry (3)Jamilah Khalaf Hamoud Alshammari (4)Abdulmajeed Salem Alsharari (5)Sultan Sayed Mogaeed Almutairi (6) (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Catheter-associated urinary tract infections (CAUTIs) pose a significant challenge in healthcare settings, leading to increased morbidity, mortality, and healthcare costs. Despite advancements in infection prevention practices, CAUTIs continue to burden healthcare systems worldwide.Methods:This research paper conducted a comprehensive review of literature to examine various nursing interventions and prevention strategies aimed at reducing CAUTIs. PubMed, CINAHL, and Cochrane Library databases were systematically searched using keywords such as "CAUTIs," "nursing interventions," and "prevention." Studies published within the last ten years were included, with a focus on randomized controlled trials, systematic reviews, and meta-analyses.Results:The review identified evidence-based nursing interventions such as proper catheter insertion and maintenance, use of catheter alternatives, and implementation of infection control measures as effective strategies for reducing CAUTIs. Additionally, nursing leadership, education, and collaboration were found to play crucial roles in CAUTI prevention.Discussion:The findings underscore the importance of a complex approach involving evidence-based nursing interventions, infection control measures, nursing leadership, education, and collaboration in reducing CAUTIs. While individual interventions have shown efficacy, a combination of approaches tailored to specific patient populations and care settings may yield the best results. Further research is acceptable to evaluate the long-term effectiveness and sustainability of CAUTI prevention strategies and to identify barriers to implementation in varied healthcare settings.